Pengaruh Model Teaching Personal Social Responsibility (Tpsr) Dalam Pembelajaran Penjas Terhadap Minat Belajar Dan Perilaku Sosial Siswa Pada Materi Bola Basket Kelas XII Di Sman 9 Mandau Kota Duri - Khofifah, Adel; Aspa, Agus Prima; Rahmatullah, M. Imam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The aim of this research is to test the influence of the TeachingPersonal Social Responsibility (TPSR) model on students' interest in learning andsocial behavior in playing basketball. In this research, researchers used the PTKresearch method. The population in this study were all class XII students of SMAN 9Mandau, Duri City. The sampling technique in this research was purposive sampling,until finally the sample in this research was class XII IPS 1, totaling 34 students. Inthis research, the design used is the Kemmis and Taggart model of PTK research(classroom action research). Researchers used the TPSR model with questionnaireinstruments for students' learning interest and social behavior, observation anddocumentation. Data analysis was carried out using the SPSS (Statistical Product andService Solution) program version 25.0 IBM for window. The average value ofstudents' learning interest and social behavior obtained after implementing the TPSRmodel increased compared to before being given treatment. The results of the research showed an increase in interest in learning and social behavior from initial conditions to cycle I then to cycle II. In the initial condition, interest in learning received a total score of 1.365 (40.15%) and social behavior received a total score of 1.557 (45.79%). After cycle I the total score for learning interest increased to 1,877 (55.21%) and social behavior increased to 2,273 (66.85%). In cycle II there was a further increase with the total learning interest score reaching 2,421 (71.21%) and social behavior reaching 2,715 (79.85%). This shows a consistent increase in participants' learning interest and social behavior from initial conditions to cycle II. So it can be concluded that the TPSR model has a significant positive influence on students' interest in learning and social behavior in playing basketball, indicating that the gradual application of this model is able to consistently improve these two aspects.Key Words: Teaching personal social responsibility (TPSR) Model, PhysicalEducation, Student interest in learning and social behavior, Basketball